Protective role of zinc during aluminum‐induced hepatotoxicity. Issue 3 (16th March 2012) - Bhasin, Punita; Singla, Neha; Dhawan, D. K.
<x xml:space="preserve">Abstract</x> The study was carried out to assess the role of zinc (Zn) in mitigating the biochemical alterations induced by aluminum (Al) in rat liver. Rats were divided into four groups: normal control, Al treated (AlCl3, 100 mg/kg b.wt./day), Zn treated (ZnSO4, 227 mg/L drinking water), and combined Al + Zn treated. Al and zinc treatments were given for a total duration of 2 months. Al treatment caused a significant increase in the activity of alkaline phosphatase (ALP), but decreased aspartate aminotransferase (AST) and alanine aminotranferase (ALT) activities, which showed the reverse trend following Zn supplementation. Levels of lipid peroxidation (LPx) and activities of catalase and glutathione‐S‐transferase (GST) were significantly decreased following Al treatment, which, however, were increased significantly in Zn co‐treated rats. Further Al exposure showed a significant increase in reduced glutathione (GSH) content as well as activities, of superoxide dismutase (SOD) and glutathione reductase (GR). However, Zn supplementation to Al‐treated rats brought down the raised levels of reduced (GSH) and SOD to within normal limits, but caused no effect on GR activity. Furthermore, Al treatment also resulted in alterations in liver histoarchitecture with disruption of hepatic cords and increased vacuolization, which were close to normal following Zn supplementation. The present study reveals that Zn is effective in attenuating the liver damage inflicted by Al toxicity. © 2012 Wiley Periodicals, Inc. Environ Toxicol 29: 320–327, 2014.